National Multicenter and Multiyear Review of Complications Following Fluoroscopic Gastrostomy in Patients Covered by Medicare and Medicaid - Khalid, Syed I.; Wu, Rita; Tasse, Jordan C.; Tabriz, David M.; Madassery, Sreekumar; Turba, Ulku C.; Arslan, Bulent (Journal of Clinical Interventional Radiology ISVIR, 2019)
Objective This study aims to assess the postoperative complication rates associated with fluoroscopically placed gastrostomy tubes.Background Fluoroscopically placed gastrostomy tubes are a relatively common procedure performed by interventional radiologists. Few studies have been performed in the United States to access the complication profile of fluoroscopically placed gastrostomy tubes.Methods Total 51 million Medicare Standard Analytic Patient Records derived from Medicare parts A and B records from 2007 to 2012 were retrospectively analyzed. Only the patients undergoing fluoroscopic gastrostomy were included in this study. Patient demographics were stratified by age, sex, comorbidities, and peri- and postoperative complications as defined by International Classification of Diseases (ICD) 9 codes.Results Total 30,327 patients undergoing fluoroscopic gastrostomy were analyzed. Perioperative complications following these procedures were low, with 61 (0.02%) patients experiencing pneumoperitoneum, 130 (0.43%) experiencing ileus, 16 (0.05%) experiencing esophageal/gastric perforation, and 30 (0.09%) patients experiencing intra-abdominal injury. Most common postoperative complications included abdominal wall pain (n = 2,808, 9.25%), bleeding (n = 1,353, 4.46%), and mechanical complications (n = 1,435, 4.73%).Conclusion Fluoroscopic guidance is a safe method for gastrostomy placement, with exceedingly low rates of peri- and postoperative complications.
Keywords: gastrostomy; G-tube; percutaneous endoscopic gastrostomy; endoscopic; fluoroscopic